The Effectiveness of Adolescent Health Booklets to Strengthen the Character of Healthy Living Behavior of Junior High School Students - Desak Made Citrawathi; Adnyana, Putu Budi; Dewi, Ni Putu Sri Ratna (LPPM Undiksha, 2022)
Teenagers today have a very permissive nature related to sex before marriage, giving rise to various health problems in adolescents. This study aimed to analyze the effectiveness of using youth health booklets in education to strengthen the character of healthy living behaviors in junior high school students. This type of research is quasi-experimental, with the research design being a randomized posttest-only control group design. The research sample was students who took part in the extracurricular activities of the AIDS and Drug Concern Student Group (KSPAN), totaling 58 people. The data collection method uses self-assessment and observation, and self-assessment sheets. Objective tests and descriptions measure students' knowledge of healthy lifestyles through questionnaires. The results showed that students who demonstrated mastery of the concept of a healthy lifestyle were in the good and very good categories of 96.67%, showed student responses in the good (27%) and very good (73%) categories, and showed good behavior (40%) and very good by 60%. The use of youth health booklets can strengthen the healthy behavior of junior high school students. This research implies that students are expected to be able to improve the application of clean and healthy living behaviors in everyday life.